2013
DOI: 10.1021/bi400338f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Isotopic Characterization of l-Proline Dehydrogenase from Mycobacterium tuberculosis

Abstract: The monofunctional proline dehydrogenase (ProDH) from Mycobacterium tuberculosis performs the flavin-dependent oxidation of L-proline to Δ1-pyrroline-5-carboxylate (P5C) in the proline catabolic pathway. The ProDH gene, prub, was cloned into the pYUB1062 vector, and the C-terminal His-tagged 37 kDa protein was expressed and purified by nickel-affinity chromatography. A steady-state kinetic analysis revealed a ping-pong mechanism with an overall kcat of 33 ± 2 sec−1 and Km values of 5.7 ± 0.8 mM and 3.4 ± 0.3 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 22 publications
2
29
0
Order By: Relevance
“…The C5 atom of THFA, which represents the hydride donor of proline, is poised 3.5 Å from the flavin N5 atom. This arrangement is consistent with a direct hydride transfer mechanism, which has been shown for PutAs (11) and monofunctional PRODHs (12). All of the interacting residues in the GsPutA-THFA and GsPutA-L-lactate complexes are conserved in PutAs and monofunctional PRODHs, and analogous interactions are observed in the THFA complexes of an Escherichia coli PutA PRODH domain construct (13) and a monofunctional PRODH (14).…”
Section: Resultssupporting
confidence: 85%
“…The C5 atom of THFA, which represents the hydride donor of proline, is poised 3.5 Å from the flavin N5 atom. This arrangement is consistent with a direct hydride transfer mechanism, which has been shown for PutAs (11) and monofunctional PRODHs (12). All of the interacting residues in the GsPutA-THFA and GsPutA-L-lactate complexes are conserved in PutAs and monofunctional PRODHs, and analogous interactions are observed in the THFA complexes of an Escherichia coli PutA PRODH domain construct (13) and a monofunctional PRODH (14).…”
Section: Resultssupporting
confidence: 85%
“…After isomerization of the enzyme-substrate complex, amine deprotonation triggers the oxidation reaction, with cleavages of the NH and CH bonds of D-leucine occurring asynchronously, as suggested by multiple deuterium kinetic isotope effects on the rate constant for flavin reduction [7]. In this respect PaDADH is similar to proline dehydrogenase [8], but different from other flavin-dependent amine oxidases, such as DAAO or monomeric sarcosine oxidase, for which amine oxidation occurs from the anionic substrate [9].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly interesting because N-terminally His-tagged TtProDH as treated with BOG was found to be a mixture of dimers and monomers [1]. Moreover, several other ProDHs have been described as dimers [21,23,39] while in some cases, the oligomerization state of ProDH was not reported [22,24,26]. SDS-PAGE indicated that the E. coli cells produce two forms of MBP-TtProDH.…”
Section: Discussionmentioning
confidence: 99%
“…All recombinant expressions of ProDH reported so far include a His-tagged protein and purification by metal affinity chromatography [18,[21][22][23][24][25][26][27]. However, obtaining soluble protein in preparative amounts has remained problematic [21,26]. Furthermore, it has been reported repeatedly that heterologous expression of ProDH in E. coli yields protein aggregates [24,27].…”
mentioning
confidence: 99%